2021
DOI: 10.1073/pnas.2103602118
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Staphylococcus aureus peptidoglycan O -acetyltransferase A as an O -acyltransferase

Abstract: The O-acetylation of exopolysaccharides, including the essential bacterial cell wall polymer peptidoglycan, confers resistance to their lysis by exogenous hydrolases. Like the enzymes catalyzing the O-acetylation of exopolysaccharides in the Golgi of animals and fungi, peptidoglycan O-acetyltransferase A (OatA) is predicted to be an integral membrane protein comprised of a membrane-spanning acyltransferase-3 (AT-3) domain and an extracytoplasmic domain; for OatA, these domains are located in the N- and C-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…In this pathway, an acetyl group from an acetyl coenzyme A donor is transported across the cytoplasmic membrane by the action of the N-terminal integral membrane domain, which belongs to the Acyl_Transf_3 (AT3; PF01757) family. The N-terminal domain of OatA then directly acetylates the C-terminal domain, which belongs to the SGNH-AT3 family and is also discussed here ( Jones et al. 2021 ).…”
Section: Introductionmentioning
confidence: 95%
“…In this pathway, an acetyl group from an acetyl coenzyme A donor is transported across the cytoplasmic membrane by the action of the N-terminal integral membrane domain, which belongs to the Acyl_Transf_3 (AT3; PF01757) family. The N-terminal domain of OatA then directly acetylates the C-terminal domain, which belongs to the SGNH-AT3 family and is also discussed here ( Jones et al. 2021 ).…”
Section: Introductionmentioning
confidence: 95%
“…The Salmonella O-antigen acetyltransferases OafB and OafA are both AT3-SGNH fusion proteins and predicted to have an 11th TMH to allow the fused SGNH domain to be located in the periplasm ( Kintz et al, 2015 ; Pearson et al, 2020 ). In contrast, Jones et al, 2021 proposed that OatA contains only 9 TMH with one large re-entrant loop; as an AT3-SGNH protein, OatA was also previously predicted to contain 11 TMH, orientating the SGNH domain in the periplasm ( Bernard et al, 2011 ; Bera et al, 2005 ). In addition, a large cytoplasmic loop was described between TMH 8 and 9 of OatA, where Oac has only short cytoplasmic loops but a longer periplasmic loop between TMH3 and 4 ( Thanweer et al, 2008 ; Rajput and Verma, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of AT3 domains consist of only an AT3 domain (standalone AT3), many are AT3 domains with an additional TMH and C-terminal, periplasmic SGNH domain attached via a periplasmic linking region (AT3-SGNH) ( Meziane-Cherif et al, 2015 ). Thanweer et al, 2008 and Jones et al, 2021 have performed PhoA-LacZɑ fusion analysis of the O-antigen acetyltransferase Oac from Shigella flexneri (a standalone AT3) and OatA from S. aureus (an AT3-SGNH), respectively. Analysis by Thanweer et al, 2008 suggested that Oac has 10 TMH, with the N- and C-termini in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations